Analysis of associations between congenital heart defect complexity and health-related quality of life using a meta-analytic strategy. (15th November 2015) - Kahr, Peter C.; Radke, Robert M.; Orwat, Stefan; Baumgartner, Helmut; Diller, Gerhard-Paul
Abstract: Background: As a consequence of heterogeneous results of relatively small individual trials, the impact of congenital heart defects (CHD) and the effect of disease severity on patient reported outcome measures (PROs) of quality of life (QoL) remains uncertain. We aimed to systematically summarize QoL data in CHD patients using meta-analytic methods. Methods and results: We performed a systematic review of the literature focusing on QoL in CHD. The search yielded 234 publications meeting the inclusion criteria, with a median of 88 patients per study (46% females, average age 24 years). In total, QoL was reported using PROs in 47, 471 CHD-patients. More than 95 different PROs were used to evaluate QoL. The most commonly used tool was the SF36 form (69 publications). Analysis of available quantitative QoL data from SF36 publications (n = 4217 CHD patients) showed that QoL was reduced in patients with moderate or complex cardiac disease (e.g. relative physical functioning scores 0.96 [0.93–0.99] and 0.91 [0.88–0.95] compared with controls), while no such effect was evident in those patients with simple cardiac lesions. Similar results were found for the general health domain of the SF36 domain. Conclusions: Despite the proliferation of QoL-studies in CHD no standardized approach for measuring and reporting QoL has emerged and the published results are heterogeneous. In aggregation, however, the results of this study suggest that QoL is impaired in moderate or complex CHD, while no such impact of CHD on QoL could be established — on average — in patients with simple defects.